Time-trends of inequalities in access to higher education (1993-2004): Signs of reversal of trends after the implementation of the "Arsenis Reform" - Γουβιάς, Διονύσης (The Greek Review of Social Research, 2010)
A very important part of the so-called «Arsenis Reform» dealt with the access to the Greek higher education, through a reorganization of the lyceum (upper-secondary school). Main aim of this study is the analysis of time-trends of access to higher education, through the system of the national (university-entrance) examinations, at three different time-spots (i.e. academic years 1993-94, 1998-99 και 2003-04), in relation to the occupational and educational grouping of the students' parents. Through the use of «indices of representation at various Higher Education establishments and/or academic departments, there is an attempt to: a) highlight the main longitudinal trends in access patterns; b) link the various scientific disciplines (and their status) to general trends in the Greek labour market; and c) provide an initial assessment of the «Arsenis Reform», as far as it concerns one of its main declared aims, that is the advancement of «equality of opportunities»